1999
DOI: 10.1016/s1010-7940(99)00310-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival after lung resection for non-small cell lung cancer in patients with microscopic residual disease at the bronchial stump

Abstract: A frozen-section analysis of the bronchial resection margin and peribronchial tissue should be made in all patients with endobronchial tumour. We suggest that patients with microscopic residual tumour and stage I or II disease should undergo re-operation, if possible. In patients with documented N2 disease we don't recommend re-operation; extending the magnitude of the resection is unlikely to alter their outcome. Choice treatment for these patients is radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
3
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 12 publications
4
48
3
3
Order By: Relevance
“…20 Many but not all studies of positive margins of surgically treated lung cancers have shown adverse impact by residual disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Microscopic residual tumor at the bronchial resection margin has then been divided into different patterns. Cotton 1 first divided microscopic residual disease into mucosal tumor (spreading from a mucosal lesion), and extramucosal microscopic residual disease (tumor involving peribronchial soft tissues or tumor within lymphatics).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…20 Many but not all studies of positive margins of surgically treated lung cancers have shown adverse impact by residual disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Microscopic residual tumor at the bronchial resection margin has then been divided into different patterns. Cotton 1 first divided microscopic residual disease into mucosal tumor (spreading from a mucosal lesion), and extramucosal microscopic residual disease (tumor involving peribronchial soft tissues or tumor within lymphatics).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Ghiribelli divided residual microscopic diseases into mucosal and extramucosal tumor, but found no difference in survival between these patterns. 4 Lymphatic space involvement at the bronchial margin has been shown to be an adverse prognostic factor in many studies. 16,9,12 Gross evaluation of bronchial margins are known to be problematic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations